Blank Spot Analysis on the Krian–Gresik Toll Road, KM 0+000–29+000 - Andre Diaz Jeremiah (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Transportation infrastructure safety, particularly the existence of blank spots on toll roads, has become a critical factor contributing to traffic accidents. This study aims to analyze blank spots on the Krian-Gresik toll road segment from STA 0+000 to STA 29+000 and their impact on traffic safety levels. The research employed a quantitative approach using descriptive-analytical survey methods. The population consisted of all road segments along the 29-kilometer Krian-Gresik toll road, with 25 sampling points selected through purposive sampling based on accident history and geometric conditions. Primary data collection utilized Total Station for measuring sight distances and curve radii, supplemented by visual documentation, while secondary data included 2024 accident reports. Data analysis involved descriptive statistics, correlation analysis, and spatial mapping using GIS technology. Results revealed that 91.7% of accidents occurred at locations with poor geometric characteristics, with the highest concentration at Kilometer 25 Lane A (3 cases). Temporal analysis showed 41.2% of accidents occurred during nighttime (18:00-24:00 WIB), indicating lighting factors influence driver visibility. Heavy trucks dominated accident involvement (41.2%), demonstrating correlation between high vehicle mass and complex road geometry. The study concludes that a significant relationship exists between blank spots and accident rates, necessitating enhanced lighting systems and specialized warning signs for heavy vehicles in geometrically complex areas to improve toll road safety.